2014
DOI: 10.1128/jcm.02209-14
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of Genotype 1 Hepatitis C Virus Subtype Misclassification by LiPA 2.0: Implications for Direct-Acting Antiviral Treatment

Abstract: The accuracy of LiPA 2.0 for hepatitis C virus 1 (HCV-1) subtype classification was analyzed. LiPA 2.0 genotype results from 101 HCV-1-infected patients were compared to genotype findings determined by direct core sequencing. Eleven (11%) samples were misclassified. Given the influence of the HCV-1-subtype in the anti-HCV therapy response, an alternative classification method is warranted.T he effect of the hepatitis C virus (HCV) genotype 1 subtype on the response to treatment can be dramatic for some direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
4
11
0
Order By: Relevance
“…In fact, an HCV genotype 4-infected patient was erroneously genotyped as HCV-1 by LiPA 2.0 herein and may have received a combination based on dasabuvir, a drug efficient in HCV-1 but not indicated for genotype 4 [ 1 – 3 ]. This finding is in agreement with that previously reported by Guelfo and colleagues, who also observed a patient erroneously genotyped by LiPA [ 4 ]. Therefore, although the concordance between NS3 sequencing and LiPA could mathematically be classified as “substancial”, it is not acceptable in the clinical practice.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In fact, an HCV genotype 4-infected patient was erroneously genotyped as HCV-1 by LiPA 2.0 herein and may have received a combination based on dasabuvir, a drug efficient in HCV-1 but not indicated for genotype 4 [ 1 – 3 ]. This finding is in agreement with that previously reported by Guelfo and colleagues, who also observed a patient erroneously genotyped by LiPA [ 4 ]. Therefore, although the concordance between NS3 sequencing and LiPA could mathematically be classified as “substancial”, it is not acceptable in the clinical practice.…”
Section: Discussionsupporting
confidence: 94%
“…Second, in a considerable proportion of individuals, HCV-1 subtypes were misclassified. Although the proportions of both HCV-1 misclassification, as well as indeterminate calls vary considerably between reports [ 4 9 , 16 , 19 ], the misclassification rate of 14% observed in this study is in accordance with a number of previously published studies [ 4 , 7 9 ]. Since the misclassification of HCV-1 subtype might lead to inadequate DAA choice or no testing of RASs, sequencing should be considered for HCV-1 infected patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Despite the epidemiological characteristics of GEHEP 005 and having included a large population of patients with chronic hepatitis C from many hospitals all over Spain to ensure the representativeness and external validity of the present study, we believe that this study has some limitations. Apart from the limitations of retrospective studies, we also found some related to the methods mainly employed herein for HCV genotyping; this limitation refers to the correct viral subtype determination of genotype 1, especially when comparing commercial to reference methods based on sequencing and phylogenetic analyses of the NS5B region of HCV . In this regard, the inclusion of HCV genotyping by sequencing‐based technologies of different viral genome regions may notably improve viral subtype knowledge, which is still important for choosing the most appropriate treatment regimen and for determining resistance‐associated substitutions (RAS).…”
Section: Discussionmentioning
confidence: 99%
“…we also found some related to the methods mainly employed herein for HCV genotyping; this limitation refers to the correct viral subtype determination of genotype 1, especially when comparing commercial to reference methods based on sequencing and phylogenetic analyses of the NS5B region of HCV. [34][35][36][37][38][39][40] In this regard, the inclusion of HCV genotyping by sequencing-based technologies of different viral genome regions may notably improve viral subtype knowledge, which is still important for choosing the most appropriate treatment regimen and for determining resistance-associated substitutions (RAS). A final limitation is that our study lacks immigration data.…”
Section: Discussionmentioning
confidence: 99%